EMPAT BERSAUDARA DALAM UTTARAKĀṆḌA: SEBUAH KAJIAN PSIKOLOGI SASTRA - Mamluatun Mamluatun Ni'mah; I Ketut Jirnaya; Komang Paramartha (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2023)
This study examines the Uttarakāṇḍa text which tells the life of Rawana's family and his three brothers who have different characters. The aim is to obtain a clear picture of personality through the four brothers in Uttarakāṇḍa through the id, ego, and superego in the theory of Literary Psychology. This research is a qualitative literature study, using observation and descriptive methods, and presented with informal methods. Furthermore, Rawana has the desire to marry Sita, looking for a way to seduce Sita to become his wife, Rawana controls his emotions when Sita does not answer his question. Furthermore, the character Kumbakarna has the desire to ask for a gift from the gods in the form of eternal sleep, he worships and obeys the orders of the gods, Kumbakarna also looks for ways to have a place to sleep. Furthermore, Surpanaka's character has the desire to cry because he is sad because his husband died, he looks for a way to complain to Rawana which makes him a widow. After getting an explanation from Rawana, he controlled the emotions he felt over the death of his lover. Furthermore, Wibhisana desired to ask for a gift from the gods in the form of the glory of knowledge, so he worshiped and obeyed the orders of the gods. When there was a meeting with Rama, Wibhisana took Rama's orders to leave the meeting place and go to Lengka.